Model Approach to Quality Provision of Public Passenger Transport - Krajnc, Roman; Sever, Drago (Promet - Traffic&Transportation, 2012)
Modern approach to transportation system research is based on the system theory. System analysis is relevant. Constant transportation technique and technology devel-opment caused by the need of conformation to the new market conditions is the basis for such an approach. The model approach for resolving the problems of public pas-senger transport is provided in a scientific report. The model of quality of passenger transport comprises the submodels which define relevant measures for the provi-sion of passenger transport quality. The synthesis of sub-model for adoption of quality standards, submodel of pas-senger demands, submodel of operation safety and securi-ty and economic submodel construct the model of quality of public passenger transport (PPT). Its evaluation has been carried out using SWOT analysis. KEY WORDS: public passenger transport, traffic, lines, network, quality, mobility